The Implementation Of Integrated Science Learning In Junior High Schools In Banda Aceh - Suwarno Suwarno (UNIVERSITAS SERAMBI MEKKAH, 2012)
The implementation of the integrated science learning is the application of science subjects that includes physics, chemistry, and biology that is being taught integratedly by emphasizing on science learning, environment, technology and society that aims to enable students to thinkscientifically, rationally and critically. This study purposes to investigated the implementation of science learning, compatibility between science learning implementation and the demand of School Unit Level Curriculum (KTSP) and the obstacles that causes the implementation of Integrated Science Learning has not been conducted in Junior High Schools in Banda Aceh. However, as the sample of research it was investigating only two teachers from each school, that are physics teacher and a teacher of biology. Research result and analysis showed that Integrated Science Learning has never been conducted based on the demands of KTSP in those schools. Most teachers have already had knowledge about Integrate Secience, but the application does not last long. This is due to differences of teachers’ scientific backgrounds, difficulty in the implementation of Integrated Science according to the demands of KTSP.